2022
DOI: 10.3390/life12020234
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Presenting Cells in Psoriasis

Abstract: Psoriasis is classically considered a chronic inflammatory skin disorder, however the identification of autoantigens in its pathogenesis established it as a T cell mediated autoimmune disease. As such professional antigen-presenting cells (APCs) are key players in the development of lesions. APCs in the skin include dendritic cells, Langerhans cells and monocytes/macrophages. In addition, epidermal keratinocytes and dermal mast cells are also endowed with antigen-presenting capacity. Skin APCs have central rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 90 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…Another positive correlation between chemerin levels, inflammatory cytokines, and C-reactive protein was reported in Ps [ 45 , 46 ]. Chemerin acts as a chemotactic factor for human blood plasmacytoid dendritic cells (pDCs), promoting their migration and recruitment in psoriatic skin [ 47 ]. Skin exhibiting early and active lesions shows high expression of chemerin in the dermis, while skin exhibiting chronic lesions has low chemerin expression, associated with few pDCs in the dermis.…”
Section: Psoriatic Patients and Obesitymentioning
confidence: 99%
“…Another positive correlation between chemerin levels, inflammatory cytokines, and C-reactive protein was reported in Ps [ 45 , 46 ]. Chemerin acts as a chemotactic factor for human blood plasmacytoid dendritic cells (pDCs), promoting their migration and recruitment in psoriatic skin [ 47 ]. Skin exhibiting early and active lesions shows high expression of chemerin in the dermis, while skin exhibiting chronic lesions has low chemerin expression, associated with few pDCs in the dermis.…”
Section: Psoriatic Patients and Obesitymentioning
confidence: 99%
“…There are abundant results reporting on the role of LCs in psoriasis [2,21]. In experimental mouse models [22], it was demonstrated that the IL-23/Th17 axis is involved in the psoriasis-like inflammation [23].…”
Section: Role Of Langerhans Cells In Psoriasismentioning
confidence: 99%
“…Extended author information available on the last page of the article disease relevant, but recently, it was shown that keratinocyteproduced IL23A in itself is sufficient to initiate psoriasis-like skin inflammation [5]. Moreover, the IL17A signaling of keratinocytes has an important contribution to the development of psoriasis in mice [6], suggesting that besides T cells, keratinocytes are also critical players in psoriasis pathogenesis [7]. Keratinocytes are either in a differentiated state or in pathological conditions; they become activated [8].…”
Section: Introductionmentioning
confidence: 99%